Simulation Study on Lightning Impulse Characteristics of Flexible Graphite Composite Grounding Materials Applied to Grounding Grid of Power System - Hu, Yuanchao; Huang, Tao; An, Yunzhu; Feng, Jianyuan; Cheng, Meng; Xie, Hongping; Shen, Wentao; Du, Changqing (Frontiers in Energy Research, 2022)
The flexible graphite composite grounding electrode is a non-metallic grounding electrode with good electrical conductivity, corrosion resistance and non-ferromagnetic properties. In order to analyze the impulse characteristics of the graphite composite grounding electrode, this paper builds a frequency domain electrical network model and an equivalent radius iterative algorithm. The calculation results are compared with CDEGS and experimental results, which verifies the validity and accuracy of the simulation model calculation. Moreover, the impulse characteristics of graphite composite grounding electrodes are analyzed by simulation, which is influenced by skin effect, inductance effect, capacitance effect and spark discharge effect. The research results show that: Inductance and skin effect can increase the grounding impedance of the grounding electrode, and capacitance and spark discharge effect can reduce it. Compared with the traditional metal grounding electrode, the graphite composite grounding electrode has a smaller skin effect and inductance effect under the action of the impulse current, and the graphite composite grounding electrode has better current flowing capability. The longer the length of the grounding electrode, the stronger the effect of the inductance effect and the skin effect. However, as the soil resistivity increases, the effects of the inductance effect and the skin effect are weakened, and the spark discharge effect is gradually enhanced and dominates. The obtained critical value of the normalized parameter of 412 kA•Ω, can be taken as the threshold to discriminate the conditions with dominate inductance effect from the conditions with dominant spark discharge effect.